ELIMINASI Cr TOTAL DALAM LARUTAN MENGGUNAKAN ADSORBEN AMPAS DAUN TEH - Isna Syauqiah; Nopi Stiyati Prihatini (INFO-TEKNIK, 2017)
Chromium is a heavy metal which if exceeded the quality standards would pollutes theenvironment, therefore the reduction of metal chromium is needed, which with the adsorptionprocess. The Adsorption could be using a natural adsorbent. One of the potential natural adsorbent which can be found in South Kalimantan is the dregs of tea leaves.This study aimed to analyze the effect of pH, adsorbent weight and contact time in the reduction of total Cr in artificial waste water and analyze the efficiency and the reduction of Cr total adsorption capacity by using adsorbents from the dregs of the black tea leaves. Before the adsorption process is started, theadsorbent should be activativated using 4% NaOH. Furthermore, the adsorption processisdobyusing the batch method with volume of liquid is 25 ml. The independent variable using pH(4,5,6,7,8), the weight of the adsorbent as much as 0.4; 0.6;0.8;1.0gram, contact time(15,30,60,90,120) minutes. Variable fixed stirring speed of 120 rpm and total Cr concentration of 10 ppm. The results showed that the largest decrease of total Cr achieved at pH4 and 0.4 gram of weight. The largest Cr adsorption at pH4 solutionis 13.18% and adsorption capacity at 0.06mg/g.  The largest efficiency and capacity achieved at 0.4 gram of weight is 12.11% and 0.06 mg/g. 60 minutes of contact time. For 60 minutes of adsorption process, resulting in 11.08% efficiency while the adsorption capacity of 0.08mg/g.